Analisis Literasi Inklusi Keuangan Syariah Pada Guru Pondok Pesantren Di Kota Bukittinggi (Studi Kasus Pada Pondok Pesantren Modern Al-Ma’arif, H. Muhammad Nadis, Dan Bai’aturridwan) - Amelia, Tisa; Izmuddin, Iiz (LPPM Institut Pendidikan Nusantara Global, 2025)
Sharia financial literacy is one of the important programs carried out by the government in order to improve the Indonesian economy in the future. This research aims to determine the level of sharia financial inclusion literacy among teachers at the Bukittinggi City Islamic Boarding School, with a sample size of 73 respondents, by conducting qualitative descriptive analysis. The author's background in discussing this title is because he sees that Islamic boarding schools as institutions or sharia-based institutions have sharia-based teachers who still lack sharia-based financial literacy and inclusion, so there are still many teachers who use conventional-based financial products rather than sharia-based ones.This research uses a qualitative approach using the Nvivo application using primary and secondary data. The analytical method used is a descriptive approach, namely identifying problems related to Islamic boarding schools currently facing using Nvivo analysis.The results of the research found that the results of the research that had been carried out on the teacher council at the Bukittinggi City Islamic Boarding School through interviews at the time of the research stated that the majority had understood sharia financial literacy because financial literacy had now been widely socialized and even some teachers already knew about sharia financial literacy. , it's just that knowledge about financial inclusion is still low